Aqueous extracts of aloe vera and Carica papaya leaves: Impacts on Coccidiosis, production and Haematology in Kabir chickens in Buea, South West Cameroon - Nghonjuyi, W.N.; Tiambo, Christian K.; Ojong, E.T.; Mankaá, C.N.; Juliano, R.S.; Lisita, F.; Kimbi, H.K. (Science Alert, 2020)
Background and Objective: The poultry industry is greatly impeded by coccidiosis and these parasites have developed resistant strains to most of the synthetic treatments applied. This study was conducted to evaluate the efficacy of aqueous leaf extracts of Carica papaya (C. papaya) and Aloe vera (A. vera) on parasitological and haematological parameters as well as growth performance of Eimeria-infected Kabir chickens. Materials and Methods: Fresh leaves were harvested and dried in gentle heat. Ground and sieved powder of fresh leaves was used to prepare the aqueous extracts. Chickens were infected with 3200 Eimeria oocysts until they began shedding oocysts in their faeces. The aqueous extracts were orally administered at doses of 0.32, 0.80 and 1.44 g–1 chicken–1. There were 3 experimental groups per extract made up of T1-T3 and two control chambers (T4, T5). Chickens of T4 were infected but not treated while T5 was the neutral group. Results: The best anticoccidial effect was observed in the T3 group which was treated with A. vera extract at a concentration of 1.44 g chicken–1 day–1. Both extracts (C. papaya and A. vera) had similar effects on growth performance with non-significant differences. Though both extracts of C. papaya and A. vera had significant effect on haematological parameters like red blood cell (RBC) and white blood cell (WBC) counts as well as haemoglobin (Hb) values, the differences were however not significant. Both extracts significantly reduced the burdens of emeriosis in chickens. Conclusion: C. papaya and A. vera aqueous extracts had good anticoccidial properties and significantly reduced the oocyst counts and improved the RBC and WBC values in the chickens.